La cultura organizacional y su influencia en el desempeño laboral en los empleados de la florícola MILROSE S.A - Chanatasig Rubio, Maricela Fernanda (2022)
This research project entitled: "The organizational culture and its influence on the employees job performance at the Florícola MILROSE S.A", aimed to determine the influence of organizational culture on the job performance of the company, using measurement tools based on performance evaluation and the Wens test, as well as statistical tools based on Pearson's Chi Square. The results obtained suggest that the level of job performance is oriented to quality, interpersonal relationships, initiative, teamwork, and organization. In the same order of things, after applying the respective organizational culture test, the following dimensions were determined: morale and satisfaction, communication, attitude to change, conflict resolution and decision making. Finally, when analyzing the correlation between the variables, it was determined that there is a relationship between organizational culture and job performance. From the above, it is concluded that organizational culture influences job performance. The dimensions with which the variables were evaluated indicate that the higher the degree of satisfaction of the physiological needs, security, affiliation, recognition and self-realization, the commitment to achieve the strategic objectives of the organization in the different financial perspectives, customers, internal processes, growth, and learning is increased.